Resistance of ewes to gastrointestinal nematode infections during the peripartum and dry periods and the performance of their lambs - GASPARINA,Jennifer Mayara (2019)
ABSTRACT This study aimed to evaluate the resistance of Texel (Tx) and Ile de France (IF) sheep to gastrointestinal nematode infections in the periparturient period and after weaning, and the performance of their lambs. Fecal samples were collected from 19 IF and 17 Texel ewes to determine fecal egg counts (FEC) and larval cultures were prepared to determine the prevalence of nematodes. The ewes were weighed to determine body weight (BW) and blood samples were taken to determine the packed cell volume (PCV) and plasm protein values (PPV). The ewes were classified into two groups by FEC (heavy and moderate infection). The IF presented higher FECs than Tx 28 and 14 days before parturition; 14, 28, and 56 days after parturition; and 28 days after weaning (P<0.05). In the weaning and dry periods, the IF presented higher PCVs than Tx (P<0.05). The PPV did not differ between the groups (P>0.05). The IF presented a higher BW than Tx 14, 28, and 42 days after parturition, and in the weaning and dry periods (P<0.05). The ewes of both breeds classified as moderately infected had the highest BW at weaning (P<0.05). IF ewes with a moderate infection produced weaning lambs that were heavier than those of Tx with the same level of infection (P<0.05). Overall, Tx ewes presented a better ability to withstand infections during the periparturient period and after weaning. Although the IF ewes presented the highest FEC and more intense periparturient rise, they managed to maintain their level of production.